Structural Virology: The Key Determinants in Development of Antiviral Therapeutics - Tanuj Handa; Ankita Saha; Aarthi Narayanan; Elsa Ronzier; Pravindra Kumar; Jitin Singla; Shailly Tomar (Viruses)
Structural virology has emerged as the foundation for the development of effective antiviral therapeutics. It is pivotal in providing crucial insights into the three-dimensional frame of viruses and viral proteins at atomic-level or near-atomic-level resolution. Structure-based assessment of viral components, including capsids, envelope proteins, replication machinery, and host interaction interfaces, is instrumental in unraveling the multiplex mechanisms of viral infection, replication, and pathogenesis. The structural elucidation of viral enzymes, including proteases, polymerases, and integrases, has been essential in combating viruses like HIV-1 and HIV-2, SARS-CoV-2, and influenza. Techniques including X-ray crystallography, Nuclear Magnetic Resonance spectroscopy, Cryo-electron Microscopy, and Cryo-electron Tomography have revolutionized the field of virology and significantly aided in the discovery of antiviral therapeutics. The ubiquity of chronic viral infections, along with the emergence and reemergence of new viral threats necessitate the development of novel antiviral strategies and agents, while the extensive structural diversity of viruses and their high mutation rates further underscore the critical need for structural analysis of viral proteins to aid antiviral development. This review highlights the significance of structure-based investigations for bridging the gap between structure and function, thus facilitating the development of effective antiviral therapeutics, vaccines, and antibodies for tackling emerging viral threats.